Sacred rivals: Catholic missions and the making of Islam in nineteenth-century France and Algeria - Peterson, Joseph W. ca. 20./21. Jh. (Oxford University Press, 2022)
Sincerely religious : Louis Veuillot and Catholic representations of Islam and empire -- God and Caesar : missionaries and militaires in colonial Algeria -- White unto harvest : religion, race, and the Jesuit mission arabe at Constantine -- Crusade of charity : liberal Catholic roots of the civilizing mission -- Conspiracy to massacre : liberal Catholics and the invention of pan-Islam -- Worthy of his hire : Charles Lavigerie, Algerian Muslims, and missionary fundraising -- Compel them to come : Algerian students and colonial racism between France and Algeria.